Dornbusch's Overshooting Model After Twenty-Five Years - Rogoff, Kenneth (IMF Working Papers; Working Paper ;, 2002)
This Mundell Fleming lecture at the International Monetary Fund's 2001 annual research conference marks the 25th anniversary of Rudiger Dornbusch's masterpiece, 'Expectations and Exchange Rate Dynamics,' a seminal contribution to both policy and research in the field of international finance. This essay provides a simple overview of the model as well as some empirics, not only on exchange rates but on measures of the paper's influence. Last, but not least, I offer some personal reflections on how Dornbusch conveyed the ideas in his 'overshooting model' to inspire a generation of students.